2010
DOI: 10.1111/j.1532-950x.2010.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from Diagnostic Laparoscopy to Laparotomy: Risk Factors and Occurrence

Abstract: A conversion rate of 21% was found in this population of dogs and cats undergoing laparoscopic diagnostic procedures. A preoperative finding of a solitary liver tumor, low total solids, and diagnosis of malignancy were all significant risk factors for conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
2
29
1
Order By: Relevance
“…The conversion of laparoscopic surgery due to hemorrhage has also been described in humans (FANFANI et al, 2012). In small animal laparoscopy, BUOTE et al (2011) have reported a conversion rate of 21%, which is different from that observed in this study (6.7%).…”
Section: Resultscontrasting
confidence: 85%
“…The conversion of laparoscopic surgery due to hemorrhage has also been described in humans (FANFANI et al, 2012). In small animal laparoscopy, BUOTE et al (2011) have reported a conversion rate of 21%, which is different from that observed in this study (6.7%).…”
Section: Resultscontrasting
confidence: 85%
“…[1][2][3][4] Elective ovariohysterectomy and ovariectomy are common surgical procedures performed in general veterinary practice. Laparoscopic ovariectomy (LOVE) and laparoscopicassisted ovariohysterectomy (LAOVH) are routinely performed for the sterilization of dogs in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Vacuolar hepatopathy was the most frequent misdiagnosis via cytologic evaluation in cats. Results of a retrospective study 6 of 94 diagnostic laparoscopies in dogs and cats showed that of 20 conversions, 13 (65%) were elective and 7 (35%) were emergent. 1 Results of another comparative retrospective study 3 including 56 dogs and cats showed that complete agreement between cytologic and histologic evaluation occurred in only 34 of 56 (61%) animals.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Cytologic evaluation of fine-needle aspirates can be a useful diagnostic tool and is commonly used to evaluate the liver. 2,6 Liver biopsy is an integral diagnostic component for characterization and management of hepatobiliary disease in dogs. However, in dogs and cats with clinical evidence of liver disease, fine-needle aspiration for cytologic examination of liver aspirates has major limitations in certain cases, including failure Diagnostic quality of percutaneous fine-needle aspirates and laparoscopic biopsy specimens of the liver in rabbits (Oryctolagus cuniculus) to identify the primary disease process and inability to provide information on tissue architecture.…”
mentioning
confidence: 99%
See 1 more Smart Citation